REPRESENTASI PESAN MORAL DALAM FILM ANIMASI JUMBO (2025): KAJIAN SEMIOTIKA DALAM MENGKONSTRUKSI SIMBOL, KARAKTER, DAN KONFLIK SEBAGAI PEMBENTUK MAKNA - Dzakirah Zayyan Afifah; Michael Jibrael Rorong (LPPM Universitas Putera Batam, 2026)
This research aims to analyze the representation of moral messages portrayed in the animated film Jumbo (2025) using Charles Sanders Peirce’s semiotic approach. The study focuses on how visual and verbal signs are constructed to convey moral meanings through symbols, characters, and conflicts within the narrative structure. A qualitative descriptive approach was employed, utilizing Peirce’s semiotic method to examine the relationship between sign, object, and interpretant in selected key scenes.The results reveal that Jumbo represents moral values emphasizing empathy, courage, and self-acceptance in the face of social injustice. Visual symbols such as color, facial expressions, and body gestures serve as significant signs that communicate universal moral meanings. The main character, Don, functions as an icon of sincerity and moral bravery, transforming from a timid boy into a figure who courageously defends goodness. Meanwhile, his internal and external conflicts symbolize human moral struggles between altruism and egoism.Through Peirce’s semiotic analysis, the study concludes that Jumbo not only offers entertainment but also delivers a profound social reflection on humanity and moral education. The film illustrates that every individual possesses moral strength to overcome rejection and discover courage through acts of kindness.Keywords: Semiotics, Charles Sanders Peirce, Animated Film Jumbo, Moral Message, Symbolism.